An Error Analysis of Students Writing Skill in Report Text: A Case Study At Ninth Grade Students of SMPN 21 Batam - Yulianza, Hani; Wilany, Eka; Shalehoddin, Shalehoddin (LINGUISTIK TERAPAN, 2024)
The objective of the study was to find out, analyze and describe the types of errors made by students in writing report text based on the theory of surface strategy taxonomy by Dulay (1982). The research methodology was descriptive qualitative research. The subject in this research was ninth grade students of SMPN 21 Batam in the academic year 2021/2022. The researcher used instrument test to collect the data. The instrument of testing in this research was writing test. The researcher asked the students to choose one topic to write a report text. Then, the researcher analyzed the students error based on the theory of surface strategy taxonomy by Dulay (1982). The result showed that there were four types of studenst errors in writing report text based on the theory of surface strategy taxonomy by Dulay (1982). There were 14 students made omission, 6 students made addition (simple addition). In misformation, there were 15 students made regularization error, 1 student made archi form, 19 students made alternating form. Besides that, there were 8 students made misordering. The students made error which are marked by omitting, adding, incorrect sentence structure, and incorrect placement in the sentence.